History Lessons During the Covid-19 Pandemic in DIY (Case Study Based on Desca Approach with the Principle of Independent Learning) - Brigida Intan Printina; Theresia Sumini (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
Research on Historical Learning During the Covid-19 Pandemic in DIY (Case Study Based on the Decca Approach) aims to describe the implementation of planning for Learning History Online in the Middle of the Covid-19 Pandemic and the application of historical learning with the principle of independent learning. The research data was collected through document analysis and questionnaires with several history teachers of Yogyakarta Senior High School (especially alumni of History Education FKIP USD), where the questionnaire questions were described based on the DESCA approach. Specifically, the DESCA approach describes the strengthening of the characters of Dignity (dignity), Energy (energy), Self Management (Self Management), Community (Community), and Awarnes (Concern). Data testing was done through data triangulation, method triangulation, and theoretical triangulation. The results of this study describe that 1) History learning generally applies distance learning to its full potential, this was expressed by history teachers through the DESCA approach; 2) History teachers do not lose the character- building process even though the learning is carried out online because they carry the principle of independent learning.